CITRA MERK DAN HARGA, DALAM MEMBANGUN KEPUASAN KONSUMEN SERTA DAMPAKNYA TERHADAP LOYALITAS PELANGGAN PADA TOKO SOMAYA DI KABUPATEN SITUBONDO - Faizatin, Firayatul; Hamdun, Edy Kusnadi; Anshory, Muhammad Iqbal (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Cosmetics are products used to care for the skin, and are also used to beautify certain parts of the body. The aim of the research is to find out: 1. Brand image has a significant influence in building consumer satisfaction.2. Price has a significant effect on consumer satisfaction. 3. Brand image has a significant effect on customer loyalty. 4. Price has a significant effect on customer loyalty. 5. Consumer satisfaction has a significant effect on customer loyalty. 6. Brand image has a significant effect on customer loyalty through consumer satisfaction. 7. Price has a significant effect on customer loyalty through consumer satisfaction. The research method used is quantitative. The data analysis technique used is convergent validity analysis. This reliability test provides an indication that the reliability of the questionnaire used as a measuring tool for each variable is in the highly correlated and acceptable category. Because each alpha value exceeds the Cronbach's Alpha value, namely: 0.70, all variables are reliable. The coefficient of determination test shows that the variables Brand Image (X1) and Price (X2) influence consumer satisfaction (Y1) by 0.80 (80%) while the remaining 20% ​​is influenced by other variables not included in this research. The variables Brand Image (X1) and Price (X2) influence customer loyalty (Y2) by 0.82 (82%) while the remaining 18% is influenced by other variables not included in this research.